SISTEM PERADILAN ISLAM DARI MASA NABI SAW. SAMPAI MASA KHULAFAURRASYIDIN - Aidil Susandi (Universitas Islam Negeri Sumatera Utara, 2022)
ABSTRACK Islam is not only a religion that regulates spiritual life, but also an order for social and state life. Justice is a central theme and is at the heart of Islamic teachings. In order to achieve a harmonious social order, Islam has a set of laws and courts that have continued to develop since the emergence of Islam itself. This paper reviews the history and development of justice in the Islamic world, from the prophetic period to the khulafaurrasyidin period (Abu Bakr, Umar, Uthman and Ali). This study uses library methode, which is processed using content analysis.